Influence of solute hydrogen on the interaction of screw dislocations with vicinal twin boundaries in nickel. (December 2019) - Li, Jiaqing; Lu, Cheng; Pei, Linqing; Zhang, Che; Tieu, Kiet
Abstract: The influence of solute H on the interaction between screw dislocations and vicinal twin boundaries in Ni bicrystals is investigated using molecular dynamics (MD) simulations. Several interaction mechanisms such as dislocation transmission, nucleation and reflection are reported for different glide planes and grain boundary (GB) structures. The presence of H tends to transform these interactions into ones involving dislocation absorption. This disorders the atomic structure of GBs and establishes a local stress state, which promotes the ultimate failure of GBs due to the formation of vacancies. These findings will deepen our understanding on the experimentally-observed H embrittlement in metallic materials. Graphical abstract: Unlabelled Image